Investigations Of NCTF With Input Shaping For Sway Control Of A Double-Pendulum-Type Overhead Crane - Mohd Ashraf, Ahmad; Raja Mohd Taufika, Raja Ismail; Mohd Syakirin, Ramli (2010)

(untitled)
This paper presents investigations into the development of hybrid control schemes for trajectory tracking and anti-swaying control of a double-pendulum-type overhead crane (DPTOC) system. A nonlinear DPTOC system is considered and the dynamic model of the system is derived using the Euler-Lagrange formulation. To study the effectiveness of the controllers, initially nominal characteristics following trajectory following (NCTF) is developed for position control of cart movement. The controller design, which is comprised of a nominal characteristic trajectory (NCT) and PI compensator, is used to make the cart motion follow the NCT. This is then extended to incorporate input shaping schemes for anti-swaying control of the system. The positive input shaper with different orders was design based on properties of the system. The results of the response with the controllers are presented in time and frequency domains. The performances of hybrid control schemes are examined in terms of level of input tracking capability, sway angle reduction and time response specifications in comparison to NCTF controller. Finally, a comparative assessment of the control techniques is discussed and presented.